PEMBUATAN FLOKULAN NON-IONIK DARI STARCH DAN ACRYLAMIDE DENGAN METODE GRAFTING TO - Sumarno Sumarno (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2006)
Synthesis of non-ionic flocculant starch-graft-polyacrylamide was produced using grafting to method. The process comprised two successive processes, i.e. synthesis of non-terminated polyacrylamide (nt-PAM) and coupling reaction. The first one was grafting onto starch. The non-terminated polyacrylamide was synthesized with solution and inverse emulsion polymerization. Temperature and time of coupling reaction were studied to evaluate the percentage of grafting efficiency (%GE) and yield (%GY), and viscosity instrinsic. The polymerization was done in glass reactor isothermally. The sample was analyzed by using FTIR. St-g-PAM was synthesized by solution and inverse emulsion polymerization. The increase of temperature and time of coupling reaction increased the percentage grafting (%GE,%GY) and viscosity instrinsic, which then finally decreased. The instrinsic viscosity of st-g-PAM that produced by emulsion inverse polimerization technic was higher than solution polymerization one.